Guideline appraisal with AGREE II: online survey of the potential influence of AGREE II items on overall assessment of guideline quality and recommendation for use - Wiebke Hoffmann-Eßer; Ulrich Siering; Edmund A. M. Neugebauer; Anne Catharina Brockhaus; Natalie McGauran; Michaela Eikermann (BMC, 2018)
Abstract Background The AGREE II instrument is the most commonly used guideline appraisal tool. It includes 23 appraisal criteria (items) organized within six domains. AGREE II also includes two overall assessments (overall guideline quality, recommendation for use). Our aim was to investigate how strongly the 23 AGREE II items influence the two overall assessments. Methods An online survey of authors of publications on guideline appraisals with AGREE II and guideline users from a German scientific network was conducted between 10th February 2015 and 30th March 2015. Participants were asked to rate the influence of the AGREE II items on a Likert scale (0 = no influence to 5 = very strong influence). The frequencies of responses and their dispersion were presented descriptively. Results Fifty-eight of the 376 persons contacted (15.4%) participated in the survey and the data of the 51 respondents with prior knowledge of AGREE II were analysed. Items 7-12 of Domain 3 (rigour of development) and both items of Domain 6 (editorial independence) had the strongest influence on the two overall assessments. In addition, Items 15-17 (clarity of presentation) had a strong influence on the recommendation for use. Great variations were shown for the other items. The main limitation of the survey is the low response rate. Conclusions In guideline appraisals using AGREE II, items representing rigour of guideline development and editorial independence seem to have the strongest influence on the two overall assessments. In order to ensure a transparent approach to reaching the overall assessments, we suggest the inclusion of a recommendation in the AGREE II user manual on how to consider item and domain scores. For instance, the manual could include an a-priori weighting of those items and domains that should have the strongest influence on the two overall assessments. The relevance of these assessments within AGREE II could thereby be further specified.